The Effect of Factor Mobility and Cast Index Index to Economic Growth in the Effect of Mediation on Labor Absorption Level - Hamid Paddu (International Journal of Advanced Science and Technology, 2020)
This study aims to influence the labor absorption rate mediation on the relation of mobility factor and construction cast index towards the economic growth. Secondary data is the main data used in this research analysis model and is sourced from various data sources, such as the Central Bureau of Statistics (BPS), the Ministry of Finance, the report of Bank Indonesia and several other sources. Data analysis method that will be used in this research is Partial Least Square with WarpPLS approach. Based on the analysis result: (1) Factor Mobility had significant and positive effect on labor absorption rate, while construction cost index had no significant effect on labor absorption rate, (2) Factor Mobility had significant and positive effect to the economic growth, (3) labor absorption rate had a significant and positive effect on the economic growth, (4) On the mediation effect, labor absorption rate had a significant mediation effect on the influence of mobility factor to economic growth, whereas labor absorption rate had no significant mediation effect on the influence of construction cost index towards the labor absorption rate. The originality of the research with the prior research lies in examining the labor absorption rate mediation effect between the relation of mobility factor and the construction cast index on the economic growth based on the economic conditions in Indonesia.